2007
DOI: 10.1007/s00436-007-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of anemia in malaria: a concise review

Abstract: Anemia is a common complication in malarial infection, although the consequences are more pronounced with Plasmodium falciparum malaria (Ghosh, Indian J Hematol Blood Tranfus 21(53):128-130, 2003). Anemia in this infection is caused by a variety of pathophysiologic mechanisms, and in areas where malaria infection is endemic, co-morbidities like other parasitic infestations, iron, folate and Vitamin B12 deficiency, deficiency of other nutrients, and anemia, which is aggravated by anti-malarial drugs both throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 48 publications
(43 reference statements)
2
77
1
2
Order By: Relevance
“…Kasturi Haldar et al, 7 and Kanjaksha Ghosh et al, [8] had discussed about multi-factorial causation of anemia in malaria patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasturi Haldar et al, 7 and Kanjaksha Ghosh et al, [8] had discussed about multi-factorial causation of anemia in malaria patients.…”
Section: Resultsmentioning
confidence: 99%
“…Further research would be needed to find exact causes of those abnormalities in patients infected with malaria parasite. Some of the studies, 6,7,8,15 had aimed for the same and had indicated immune mechanism, 8,15 and role of inflammatory markers, 6,7,8 in causation of hematological disturbances in patients suffering from malaria. In our study, most of the patients were anemic.…”
Section: Resultsmentioning
confidence: 99%
“…The malariaspecific factors are described in detail in a review by Ghosh and Ghosh. 19 One of the key features that explain chronic anemia as one complication of severe malaria is a low reticulocyte response and high serum erythropoietin levels and ongoing hemolysis. 20 These factors interact with other coexisting infections and nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple causes of anemia in a malaria infection 18 ( Figure 3) and it is likely that several of the mechanisms are involved in the pathogenesis of SMA.…”
Section: Severe Malarial Anemiamentioning
confidence: 99%